National Regulation of Satellite Ground Stations : A Global Comparison - Rasila, Tommi; Ojala, Arto (Palgrave Macmillan, 2024)
Ground stations play a key role in space ecosystems by enabling communications with satellites. Due to the increasing number of LEO satellites, the number of ground stations is also growing. However, legislation and regulations related to ground stations have fallen behind due to this rapid development. Furthermore, different countries have varying regulations for ground stations, making it difficult for firms operating ground stations to establish and conduct successful global operations. In this study, we employ a qualitative approach to collect data and compare ground station regulations in 20 different countries. Based on our findings, we categorize regulations into specific, general, and hidden categories and explain their impact on ground station operations. Secondly, we highlight the possibilities for foreign operators to act and establish ground stations in different countries. Thirdly, we emphasize the need for harmonizing regulations globally.
Keywords: Ground stations; Regulations; Satellites; LEO; fi=Kansainvälinen liiketoiminta|en=International Business|